(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This article briefly presents a preliminary comparative study between the similarities and peculiarities of Portugal’s Teatro Dom Roberto and Brazil’s Mamulengo from Pernambuco. The aim of this research is to understand the relationships and similarities between these popular folk performances. The play, improvisation, historical details, and facts will be aspects to be analyzed in each manifestation, relating them to their cultural differences.